PELATIHAN PEMASARAN PADA UMKM SUMBER SEHAT SEBAGAI CARA UNTUK MEMPERKENALKAN PRODUK: MARKETING TRAINING FOR SUMBER HEALTH SMEs AS A WAY TO INTRODUCE PRODUCTS - Alvian Alrasid Ajibulloh; Angga Intueri Mahendra P; Nurfian Yudhistira (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Introduction: The pandemic has hurt MSMEs. Even though MSMEs are currently fully operational, many problems still result in the low competitiveness of their business products, one of which is Sumber Sehat UMKM. Purpose: This activity aims to provide knowledge about marketing strategies and develop several forms of output for promotional purposes. Method: The method provided training and work initiated by Amikom Yogyakarta University and carried out in Plumbon Kidul Village RT 03 / RW 014, Mororejo, Kec. Paste, Kab. Sleman, Yogyakarta. Result: This activity results in partners getting a business identity through a logo design. Update the packaging design. Have a P-IRT and have promotional content in the form of product photos and videos. Not only that, managers and the community also received new knowledge regarding marketing strategies delivered through on-site seminars. And all of these activities have also been published in the mass media.